URGENSI PERGURUAN TINGGI BAGI MAHASANTRI DI ERA SOCIETY 5.0 - Alkiromah W, Berliani Aslam; Warsah, Idi (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2023)
Colleges play a crucial role for mahasantri (Islamic college students) in the era of Society 5.0. The advancements in technology and digitalization have transformed various aspects of life, including education. Colleges have evolved beyond being mere institutions of formal education; they now serve as multidisciplinary learning centers that encourage mahasantri to adapt and contribute to an advanced society. The urgency of colleges for mahasantri lies in accessing future-oriented knowledge and skills, as well as developing character and values in Society 5.0. In the era of Society 5.0, colleges need to swiftly adapt by providing inclusive, technology-driven, and collaborative learning environments. They must also update their curricula in line with the latest technological and social trends. By providing access to relevant knowledge and skills, and aiding in the development of necessary character traits, colleges empower mahasantri to become influential actors in Society 5.0. This research aims to explore the urgency of colleges for mahasantri in the era of Society 5.0 and the significance of skill and character development. The research employs a qualitative approach through literature review, utilizing secondary data from relevant national journals. The findings of this study are expected to enhance understanding of the urgency of colleges for mahasantri in the era of Society 5.0 and provide guidance in developing relevant curricula and learning environments.